Antioxidant activity, total phenolic, flavonoid, and caffeine contents of robusta coffee (Coffea canephora) fermented with lactic acid bacteria - Aisyah, Nadira; Sunarti, Titi Candra; Meryandini, Anja (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2025)
Robusta coffee is widely cultivated in Indonesia, but it struggles to dominate the global market due to its bitterness, slightly sour taste, and higher caffeine content. Coffee bean fermentation can be done to reduce undesirable characteristics in robusta coffee. This study aimed to evaluate the effects of lactic acid bacteria fermentation on the quality of coffee and its brewing characteristics, comparing it to spontaneous fermentation. The goal was to explore the potential of fermented coffee beans as functional beverages with health benefits. Three lactic acid bacteria (LAB) isolates were tested, and Lactiplantibacillus plantarum H 2.34 was identified as the most effective starter culture for coffee fermentation. After 12 hours of fermentation using coffee mucilage, LAB growth was significantly enhanced. A significant increase in flavonoid content was observed in coffee fermented with the starter culture. All brewed coffee samples demonstrated strong antioxidant activity, and LAB fermentation successfully reduced caffeine content by 4.85%. These results suggest that fermented robusta coffee could offer functional health benefits while improving its sensory profile.